2020
DOI: 10.1192/bjp.2019.267
|View full text |Cite
|
Sign up to set email alerts
|

In the aftermath of clozapine discontinuation: comparative effectiveness and safety of antipsychotics in patients with schizophrenia who discontinue clozapine

Abstract: Background Although clozapine is often discontinued, there is a paucity of guidelines and evidence on treatment options after clozapine discontinuation. Moreover, it is currently unknown whether reinstating clozapine in patients formerly using clozapine should be avoided. Aims To compare the real-world effectiveness of antipsychotics after clozapine cessation. Method From Finnish registry data (1995–2017), we identified 2250 patients with schizophrenia who had been usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…Quetiapine could be frequently initiated due to the favorable side‐effect profile, compared with other antipsychotics 37 . The findings are also in line with a recent Finnish registry study showing that restarting clozapine and switching to oral olanzapine is associated with a lower risk of psychiatric ward re‐admission, treatment failure, and mortality, compared with switching to other antipsychotics 23 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Quetiapine could be frequently initiated due to the favorable side‐effect profile, compared with other antipsychotics 37 . The findings are also in line with a recent Finnish registry study showing that restarting clozapine and switching to oral olanzapine is associated with a lower risk of psychiatric ward re‐admission, treatment failure, and mortality, compared with switching to other antipsychotics 23 …”
Section: Discussionsupporting
confidence: 76%
“…37 The findings are also in line with a recent Finnish registry study showing that restarting clozapine and switching to oral olanzapine is associated with a lower risk of psychiatric ward re-admission, treatment failure, and mortality, compared with switching to other antipsychotics. 23 We found that polypharmacy without clozapine was associated with similar persistence relative to monotherapy in patients discontinuing clozapine. Polypharmacy may reduce symptoms more effectively than monotherapy due to better receptor occupancy, but this could also lead to more or relatively severe side effects, resulting in no difference in persistence.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…83,84 It is recognized that the best treatment for psychosis after clozapine has been discontinued is a repeated trial of clozapine. 85 Given the risks associated with treatment failure in our patient group, we took an active approach to supporting neutrophil counts, often using G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“… 83 , 84 It is recognized that the best treatment for psychosis after clozapine has been discontinued is a repeated trial of clozapine. 85 …”
Section: Discussionmentioning
confidence: 99%